Method for inducing osteogenic differentiation of mesenchymal stem cells by ultrasonic piezoelectric material
By preparing piezoelectric nanomaterials loaded with barium titanate and doped with calcium and zirconium, its self-generating properties induce osteogenic differentiation of bone marrow mesenchymal stem cells under ultrasound, it solves the difficulty in accurately simulate bone in the existing technology. The problem of the microenvironment of the tissue surface potential has achieved efficient results in bone healing and repair of pulp damage.
Patent Information
- Application Number
- CN202411538946.3
- Authority / Receiving Office
- CN · China
- Patent Type
- Applications(China)
- Current Assignee / Owner
- Filing Date
- 2024-10-31
- Publication Date
- 2025-02-11
AI Technical Summary
Existing piezoelectric materials have problems that are difficult to accurately simulate in simulating and restoring the complex and variable surface potential microenvironment of bone tissue, limiting their direct and efficient role in promoting bone healing.
By preparing piezoelectric nanomaterials with barium titanate-loaded graphene oxide and doped with calcium and zirconium, its self-generating properties are used to induce osteogenic differentiation of bone marrow mesenchymal stem cells under ultrasound action.
Significantly improves conductivity and piezoelectric properties, enhances conductivity and covalence, promotes osteogenic differentiation of bone marrow mesenchymal stem cells, improves the effect of pulp injury repair, and shows excellent piezoelectricity in bone tissue engineering performance.
Smart Images

Figure CN119405899A_ABST
Abstract
Description
Technical Field
[0001] The invention belongs to the field of nanoscience and technology, and specifically relates to a method and application of using ultrasonic piezoelectric materials to induce osteogenic differentiation of bone marrow mesenchymal stem cells. Background Art
[0002] The piezoelectric material BCZT / GO, as a non-centrosymmetric crystal innovation, shows high potential in sonosensing technology and is used in sonodynamic therapy. Its unique structure promotes efficient separation of electrons and holes, overcoming the problems of fast composite and low efficiency of traditional barium titanate. The synthesis strategy of BCZT / GO significantly enhances the piezoelectric catalytic performance by loading graphene oxide and zirconium calcium doping, providing a powerful tool for biomedical process intervention. Although current piezoelectric material technology integrates growth factors and drugs to enhance efficacy, BCZT / GO piezoelectric materials have shown the potential for surface charge generation under ultrasound during exploration. However, the challenge it faces is that it is difficult to accurately simulate and restore the complex and changeable surface potential microenvironment of bone tissue. This limitation directly restricts the direct and efficient role of this material in promoting bone healing. Summary of the invention
[0003] The purpose of the present invention is to provide a method and application of inducing osteogenic differentiation of bone marrow mesenchymal stem cells using ultrasonic piezoelectric materials, so as to solve the problems raised in the above-mentioned background technology.
[0004] In order to achieve the above object, the present invention provides the following technical solution: a method for inducing osteogenic differentiation of bone marrow mesenchymal stem cells using ultrasonic piezoelectric materials, and the specific steps of the preparation method are as follows:
[0005] S1: Preparation of solution; TiCl4 and ZrCl2 were dissolved in anhydrous ethanol and deionized water, mixed and magnetically stirred at 100°C for 30 minutes to promote the reaction, then the pH was adjusted and NaOH and PVP were added, stirred for 10 minutes to help the formation of nanomaterials;
[0006] S2: Introduction of graphene oxide and doping ions: After GO is dispersed, ultrasonic treatment is performed, and CaCl2 and ZrCl2 are added for stirring, so that the doping ions are evenly distributed on the GO surface and solution;
[0007] S3: hydrothermal reaction and post-treatment: The product was obtained by hydrothermal reaction at 180°C / 12h, washed to neutrality, and dried at 80°C to obtain barium titanate / GO doped calcium zirconium piezoelectric material.
[0008] 2. The method for inducing osteogenic differentiation of bone marrow mesenchymal stem cells using ultrasonic piezoelectric materials according to claim 1, characterized in that the specific steps of introducing graphene oxide and doping ions in S2 are as follows:
[0009] Step 1: Dispersion of graphene oxide
[0010] Accurately weigh 100 mg of GO and slowly add it to 30 mL of deionized water;
[0011] The mixed solution was ultrasonicated using an ultrasonic processor for 10 minutes to ensure that GO was evenly dispersed in water to form a stable GO dispersion;
[0012] Step 2: Preparation of doping ions
[0013] Accurately weigh 0.166 g of CaCl2 and 0.373 g of ZrCl2-7H2O;
[0014] Add the two salts separately or simultaneously into an appropriate amount of deionized water to ensure complete dissolution;
[0015] Step 3: Mixing and stirring of doping ions
[0016] Slowly add the doping ion solution prepared in step 2 to the GO dispersion prepared in step 1;
[0017] The mixed solution was stirred using a magnetic stirrer at 100 rpm and 100 °C for 30 min. This step was intended to allow the doping ions to be evenly distributed on the surface of GO and throughout the solution, promoting their interaction with GO and possible doping processes.
[0018] Preferably, the specific steps of the hydrothermal reaction and post-treatment in S3 are as follows:
[0019] Step 1: Hydrothermal reaction
[0020] Carefully transfer all the mixed solutions to the high-temperature hydrothermal reactor to ensure that no solution remains;
[0021] Seal the reactor and adjust the heating system to gradually raise the internal temperature of the reactor to 180 degrees Celsius;
[0022] The reaction was maintained at this temperature for 12 hours, during which time barium titanate grew on the surface of GO and was doped with calcium and zirconium to form the desired nanocomposite material;
[0023] Step 2: Washing the precipitate
[0024] After the reaction is completed, the reactor is cooled naturally to room temperature, and the product is taken out of the reactor. The product is repeatedly washed with deionized water to remove residual unreacted substances, ions and other impurities. Then, it is further washed with anhydrous ethanol until the pH value of the washing liquid reaches 7, indicating that the precipitate has been washed clean.
[0025] Step 3: Drying
[0026] The washed precipitate is transferred to a dry and clean container; the container is placed in an oven at 80°C for drying for 12 hours; after drying, the product is taken out to obtain the final piezoelectric nanomaterial of barium titanate loaded with graphene oxide and doped with calcium and zirconium.
[0027] Preferably, the piezoelectric material prepared based on the above preparation method has a self-generating property under the action of ultrasound to induce osteogenic differentiation of bone marrow mesenchymal stem cells (BMSC) to achieve dental pulp damage repair, wherein the bone marrow cell stimulation and detection method steps are as follows:
[0028] A1: BMSC inoculation, group culture and ultrasonic stimulation; BMSC were inoculated in 24-well plates and cultured and then divided into five groups. The material group was added with 50ug / ml solution. After 8 hours, the US group and the material + US group were ultrasonicated according to the set parameters, and the process was repeated every other day until the 7th day.
[0029] A2: Continued culture and differentiation of BMSCs: BMSCs were continuously cultured after ultrasound and the signs of osteogenic differentiation were observed for 7 days;
[0030] A3: Alizarin red method to detect BMSC differentiation into osteoblasts: Alizarin red was used to stain BMSC to measure osteogenic differentiation, and the red particles were observed under a microscope to record the differentiation.
[0031] Preferably, the specific steps of inoculation, grouping culture and ultrasonic stimulation of BMSCs in A1 are as follows:
[0032] Step 1: Cell inoculation and culture:
[0033] Bone marrow mesenchymal stem cells were evenly seeded into a 24-well plate with a moderate cell density in each well;
[0034] The well plate was placed in a cell culture incubator at 37°C and 5% CO2 for 24 hours until the cells adhered;
[0035] Step 2: Grouping and material processing:
[0036] The cells were divided into five groups: control group, US group, BCZT / GO group, US+BTO group, and US+BCZT / GO group; for the groups containing materials (BCZT / GO, US+BTO, and US+BCZT / GO), material solutions with a concentration of 50ug / ml were added to the corresponding wells;
[0037] Step 3: Ultrasonic stimulation:
[0038] Eight hours after the addition of the materials, ultrasound stimulation was performed on the US, US+BTO, and US+BCZT / GO groups; the ultrasound parameters were set to 50% Duty Cycle, 1.0 MHz, and 1.5 W / cm 2, lasting for 5 minutes. After the stimulation was completed, the well plate was returned to the cell culture incubator for continued culture. During the subsequent culture process, ultrasonic stimulation was repeated every two days until the 7th day.
[0039] Preferably, the continued culture and differentiation of BMSC in A2 means that after the ultrasonic stimulation is completed, the BMSC are placed in a constant temperature incubator at 37°C and 5% CO2 for continued culture to support their growth and differentiation process. During this period, the cell status is closely monitored and regularly checked to ensure that the culture environment is stable and suitable. At the end of the culture on the 7th day, the differentiation of BMSC in each group is observed, with special attention paid to whether there are signs of differentiation into osteoblasts, such as changes in cell morphology and expression of specific markers, to evaluate the effects of different treatment conditions on the osteogenic differentiation of BMSC.
[0040] Preferably, the specific steps of detecting the differentiation of BMSC into osteoblasts by the Alizarin Red method in A3 are as follows:
[0041] Step 1: Sample preparation:
[0042] Remove the culture medium from the well plate and gently rinse the BMSC culture dish twice with PBS to remove the residual culture medium and impurities;
[0043] Step 2: Cell fixation:
[0044] Add an appropriate amount of 95% ethanol to each well and fix the cells for 10 minutes; after fixation, rinse the cells three times with double distilled water to remove residual ethanol;
[0045] Step 3: Alizarin red staining:
[0046] Add 0.1% Alizarin Red-Tris-HCl solution (pH 8.3) to each well, making sure that the solution covers the entire bottom of the well, and incubate the plate at 37°C for 30 minutes to allow Alizarin Red to bind to calcium salts in osteoblasts to form a red precipitate;
[0047] Step 4: Observe and record:
[0048] After staining, the cells were gently rinsed with double distilled water to remove unbound alizarin red dye; the red ALP-positive particles in the cytoplasm of osteoblasts were observed under a microscope, and the differentiation of cells in each group was recorded.
[0049] The beneficial effects of the present invention are as follows:
[0050] 1. The present invention significantly improves the conductivity of barium titanate nanomaterials by doping calcium zirconium on the basis of barium titanate and loading graphene oxide. Differential charge density analysis reveals that doping and heterojunction promote electron interaction, the Fermi level state density surges, and the conductivity and covalency are enhanced. The piezoelectric coefficient d33 is 2.56 times higher than that of pure barium titanate. The self-generating characteristics are used to simulate the bioelectric environment of bone tissue, which opens up a new way to induce osteogenic differentiation of bone marrow mesenchymal stem cells and repair of dental pulp injuries, and is expected to promote the reconstruction and regeneration of oral bone tissue.
[0051] 2. The present invention uses BCZT / GO nanomaterials to disperse evenly and have a moderate particle size. Its piezoelectric coefficient is about 2.56 times higher than that of BTO, showing excellent piezoelectric performance. This material not only has excellent biocompatibility, but also has the mechanical strength to meet the needs of bones. It can generate electrical signals autonomously to promote cell response. In bone tissue engineering, BCZT / GO significantly promotes the differentiation of bone marrow mesenchymal stem cells into osteoblasts, which is 20% higher than traditional BTO, providing an innovative way for remote biological regulation without power supply. The self-generating characteristics of piezoelectric materials under the action of ultrasound are used to stimulate bone marrow cells, thereby inducing bone marrow mesenchymal stem cells (BMSC) to differentiate into osteoblasts, and then applied to the technical direction of oral osteochondral repair. BRIEF DESCRIPTION OF THE DRAWINGS
[0052] Figure 1 It is a schematic diagram of the overall process of the preparation method of the present invention;
[0053] Figure 2 A transmission electron microscope schematic diagram of a novel piezoelectric nanomaterial of barium titanate loaded graphene oxide doped with zirconium and calcium (BCZT / GO) prepared by a hydrothermal method of the present invention;
[0054] Figure 3 A schematic diagram of a scanning electron microscope photograph of a novel piezoelectric nanomaterial of barium titanate loaded with graphene oxide doped with zirconium and calcium (BCZT / GO) prepared by a hydrothermal method of the present invention;
[0055] Figure 4 Schematic diagram of particle size distribution of a novel piezoelectric nanomaterial of barium titanate loaded graphene oxide doped with zirconium and calcium (BCZT / GO) prepared by a hydrothermal method of the present invention;
[0056] Figure 5 This is an element mapping (EDS) of a novel piezoelectric nanomaterial of barium titanate loaded graphene oxide doped with zirconium and calcium (BCZT / GO) prepared by a hydrothermal method of the present invention;
[0057] Figure 6It is a schematic diagram of the XPS spectrum of the novel piezoelectric nanomaterial of barium titanate loaded graphene oxide doped with zirconium and calcium (BCZT / GO) prepared by the hydrothermal method of the present invention;
[0058] Figure 7 The schematic diagram of the XRD spectrum of the novel piezoelectric nanomaterial of barium titanate loaded graphene oxide doped with zirconium and calcium (BCZT / GO) prepared by the hydrothermal method of the present invention;
[0059] Figure 8 A schematic diagram of differential charge density of a novel piezoelectric nanomaterial of barium titanate loaded graphene oxide doped with zirconium and calcium (BCZT / GO) prepared by a hydrothermal method of the present invention;
[0060] Fig. 9 Schematic diagram of the density of states (DOS) of BTO, BZT, BCZT, and BCZT / GO calculated by the first principles simulation of the present invention;
[0061] Fig.10 Schematic diagram of the density of states (PDOS) of barium titanate (BTO), barium titanate doped with zirconium ions (BZT), barium titanate doped with zirconium ions and calcium ions (BCZT), and barium titanate doped with zirconium ions and calcium ions and loaded with graphene oxide (BCZT / GO) calculated by the first principles simulation of the present invention;
[0062] Fig.11 The atomic force microscope morphology of BCZT / GO of the present invention, the amplitude diagram of the piezoelectric microscope (scale bar is 200nm), and the schematic diagram of the piezoelectric response phase;
[0063] Fig.12 The piezoelectric response PFM of the BCZT / GO nanostructure of the present invention, the PFM curve of the butterfly amplitude ring of BCZT / GO, and the schematic diagram of the BTO and d33 coefficients of BCZT / GO;
[0064] Fig.13 Schematic diagram of the photocurrent of BTO, BZT and BCZT / GO nanoparticles under full-spectrum light irradiation, and the impedance curve of BTO, BZT and BCZT / GO nanoparticles of the present invention;
[0065] Fig.14 This is a schematic diagram of the results of alkaline phosphatase staining of bone marrow mesenchymal stem cells after the new piezoelectric nanomaterial prepared by the hydrothermal method of the present invention, barium titanate loaded graphene oxide doped with zirconium and calcium (BCZT / GO), is applied to the bone marrow mesenchymal stem cells. DETAILED DESCRIPTION
[0066] The following will be combined with the drawings in the embodiments of the present invention to clearly and completely describe the technical solutions in the embodiments of the present invention. Obviously, the described embodiments are only part of the embodiments of the present invention, not all of the embodiments. Based on the embodiments of the present invention, all other embodiments obtained by ordinary technicians in this field without creative work are within the scope of protection of the present invention.
[0067] like Figures 1 to 14 As shown, the embodiment of the present invention provides a method for inducing osteogenic differentiation of bone marrow mesenchymal stem cells using ultrasonic piezoelectric materials. The specific steps of the preparation method are as follows:
[0068] S1: Preparation of precursor solution: dissolving TiCl4 and ZrCl2 in anhydrous ethanol and deionized water to prepare uniform titanium chloride and barium chloride solutions;
[0069] S2: Mixing and preliminary reaction: Mix the two solutions and stir them magnetically at 100 rpm for 30 min at 100 °C to promote ion mixing and preliminary reaction;
[0070] S3: pH adjustment and addition of additives: NaOH and PVP were added to adjust the pH, stirred at 100 °C for 10 minutes, and PVP was introduced to assist the formation of nanomaterials;
[0071] S4: Introduction of graphene oxide and doping ions: After GO is dispersed, ultrasonic treatment is performed, and CaCl2 and ZrCl2 are added for stirring, so that the doping ions are evenly distributed on the GO surface and solution;
[0072] Dispersion of graphene oxide: 100 mg of GO was added to 30 mL of deionized water and sonicated for 10 min to ensure that GO was evenly dispersed in the water.
[0073] Mixing of doping ions: 0.166 g (2.25 mmol) of CaCl2 and 0.373 g (1 mmol) of ZrCl2-7H2O were mixed with the GO dispersion and stirred at 100 rpm and 100 °C for 30 min to make the doping ions evenly distributed on the GO surface and in the solution.
[0074] S5: hydrothermal reaction and post-treatment: hydrothermal reaction at 180°C / 12h to obtain the product, wash to neutrality, and dry at 80°C to obtain barium titanate / GO doped calcium zirconium piezoelectric material.
[0075] The particle size of the piezoelectric nanomaterial of barium titanate loaded with graphene oxide and doped with calcium and zirconium is 200 to 400 nanometers, and the piezoelectric performance of the piezoelectric nanomaterial is 2.56 times higher than that of barium titanate.
[0076] in, Figure 8Schematic diagram of differential charge density of a novel piezoelectric nanomaterial of barium titanate loaded graphene oxide doped with zirconium and calcium (BCZT / GO) prepared by a hydrothermal method of the present invention; (the doping of Ca and Zr elements and the heterojunction formed with graphene oxide lead to an increase in the amount of electron interaction transfer within the structure.)
[0077] The specific steps for preparing the precursor solution in S1 are as follows:
[0078] Step 1: Preparation of titanium chloride solution
[0079] Weigh 1.809 g (9 mmol) of TiCl4 using a precise balance, making sure the amount is accurate;
[0080] Slowly add the weighed TiCl4 into 10 ml of anhydrous ethanol while gently stirring until the TiCl4 is completely dissolved to form a colorless or light yellow uniform titanium chloride solution.
[0081] Step 2: Preparation of barium chloride solution
[0082] Weigh 3.12 g (12.75 mmol) of BaCl2 using a precise balance, making sure the amount is accurate;
[0083] Gradually add the weighed BaCl2 into 30 ml of deionized water while stirring continuously until the BaCl2 is completely dissolved to form a transparent barium chloride solution.
[0084] The steps for preparing the precursor solution are precise, ensuring the purity and concentration of the reactants. TiCl4 and BaCl2 are dissolved in anhydrous ethanol and deionized water, respectively, to promote ion dispersion and mixing, providing a uniform environment for subsequent reactions. This method simplifies the operation process, improves the preparation efficiency, lays a good foundation for the subsequent formation of nanomaterials, and ensures the performance and stability of the materials.
[0085] The mixing and preliminary reaction in S2 refers to slowly mixing the carefully prepared titanium chloride solution and barium chloride solution in S1, and then placing them in a container equipped with a magnetic stirrer, and stirring the mixed solution for 30 minutes under strictly controlled conditions, i.e., setting the stirring speed to 100 rpm and maintaining the ambient temperature at 100°C. This process is designed to ensure that the ions in the two solutions can fully contact and mix, and initiate a preliminary chemical reaction, laying a solid foundation for the subsequent formation of nanomaterials.
[0086] The mixing and preliminary reaction steps are rigorous to ensure that the ions are fully contacted and reacted. The stirring speed and temperature are precisely controlled to promote uniform mixing of the solution and accelerate the preliminary chemical reaction. This process lays a solid foundation for the formation of nanomaterials and improves the controllability and consistency of material preparation. This method optimizes the reaction conditions, improves the performance and stability of nanomaterials, and is of great significance to materials science research.
[0087] Among them, the adjustment of pH value and addition of additives in S3 refers to the careful addition of 3.6 grams (i.e. 90 mmol) of NaOH and 1.2 grams of polyvinyl pyrrolidone (PVP) to the solution mixed with titanium chloride and barium chloride. Subsequently, the solution is placed on a magnetic stirrer heated to 100°C and set to 100 rpm, and stirred for 10 minutes. This step is intended to accurately control the pH value of the solution and optimize the solution environment by introducing PVP as a surfactant, thereby providing strong support for the successful synthesis of subsequent nanomaterials.
[0088] The specific steps of introducing graphene oxide and doping ions in S4 are as follows:
[0089] Step 1: Dispersion of graphene oxide
[0090] Accurately weigh 100 mg of GO (graphene oxide) and slowly add it to 30 ml of deionized water;
[0091] The mixed solution was ultrasonicated using an ultrasonic processor for 10 minutes to ensure that GO was evenly dispersed in water to form a stable GO dispersion;
[0092] Step 2: Preparation of doping ions
[0093] Accurately weigh 0.166 g (2.25 mmol) of CaCl2 and 0.373 g (1 mmol) of ZrCl2-7H2O.
[0094] Add the two salts separately or simultaneously to an appropriate amount of deionized water (if they dissolve quickly in water and do not require additional solvent), ensuring complete dissolution;
[0095] Step 3: Mixing and stirring of doping ions
[0096] Slowly add the doping ion solution prepared in step 2 to the GO dispersion prepared in step 1;
[0097] The mixed solution was stirred with a magnetic stirrer at 100 rpm and 100 °C for 30 min. This step was to allow the doping ions (Ca 2+ and Zr 4+) can be evenly distributed on the surface of GO and throughout the solution, promoting their interaction with GO and possible doping process.
[0098] The introduction steps of graphene oxide and doping ions are refined to ensure efficient and uniform mixing. Ultrasonic treatment promotes GO dispersion and improves stability; doping ions are precisely formulated to ensure accurate stoichiometry. Magnetic stirring promotes uniform distribution of ions and enhances the interaction between GO and ions, providing a good foundation for subsequent hydrothermal reactions. This method improves the preparation efficiency and performance of nanocomposites and has broad application prospects.
[0099] The specific steps of the hydrothermal reaction and post-treatment in S5 are as follows:
[0100] Step 1: Hydrothermal reaction
[0101] Carefully transfer all the mixed solutions to the high-temperature hydrothermal reactor to ensure that no solution remains;
[0102] The reactor was sealed and the heating system was adjusted to gradually raise the internal temperature of the reactor to 180 degrees Celsius.
[0103] The reaction was maintained at this temperature for 12 hours, during which time barium titanate grew on the surface of GO and was doped with calcium and zirconium to form the desired nanocomposite material;
[0104] Step 2: Washing the precipitate
[0105] After the reaction is completed, the reactor is cooled naturally to room temperature, and the product is taken out of the reactor. The product is repeatedly washed with deionized water to remove residual unreacted substances, ions and other impurities. Then, it is further washed with anhydrous ethanol until the pH value of the washing liquid reaches 7, indicating that the precipitate has been washed clean.
[0106] Step 3: Drying
[0107] The washed precipitate is transferred to a dry and clean container; the container is placed in an oven at 80°C for drying for 12 hours; after drying, the product is taken out to obtain the final piezoelectric nanomaterial of barium titanate loaded with graphene oxide and doped with calcium and zirconium.
[0108] The hydrothermal reaction and post-treatment process are rigorous to ensure the high-quality preparation of nanocomposites. Through precise temperature control and reaction time, the growth and doping of barium titanate on the GO surface are promoted to improve the material performance. The washing and drying steps completely remove impurities to ensure the purity and stability of the product. The nanomaterials prepared by this method have wide application potential in the fields of piezoelectricity and catalysis, and promote the development of new material technology.
[0109] Among them, the piezoelectric material prepared based on the above preparation method has the characteristic of self-generating electricity under the action of ultrasound to induce the osteogenic differentiation of bone marrow mesenchymal stem cells (BMSC) to achieve dental pulp damage repair, wherein the bone marrow cell stimulation and detection method steps are as follows:
[0110] A1: BMSC inoculation, group culture and ultrasonic stimulation; BMSC were inoculated in 24-well plates and cultured and then divided into five groups. The material group was added with 50ug / ml solution. After 8 hours, the US group and the material + US group were ultrasonicated according to the set parameters, and the process was repeated every other day until the 7th day.
[0111] A2: Continued culture and differentiation of BMSCs: BMSCs were continuously cultured after ultrasound and the signs of osteogenic differentiation were observed for 7 days;
[0112] A3: Alizarin red method to detect BMSC differentiation into osteoblasts: Alizarin red was used to stain BMSC to measure osteogenic differentiation, and the red particles were observed under a microscope to record the differentiation.
[0113] Piezoelectric nanomaterials made of barium titanate loaded with graphene oxide and doped with calcium and zirconium stimulate bone marrow mesenchymal stem cells to differentiate into osteoblasts, which is about 20% higher than that of barium titanate.
[0114] The specific steps of inoculation, group culture and ultrasonic stimulation of BMSCs in A1 are as follows:
[0115] Step 1: Cell inoculation and culture:
[0116] Bone marrow mesenchymal stem cells (BMSCs) were evenly seeded into a 24-well plate with a moderate cell density in each well; the plate was placed in a cell culture incubator at 37°C and 5% CO2 for 24 hours until the cells adhered to the wall;
[0117] Step 2: Grouping and material processing:
[0118] The cells were divided into five groups: control group, US group, BCZT / GO group, US+BTO group, and US+BCZT / GO group; for the groups containing materials (BCZT / GO, US+BTO, and US+BCZT / GO), material solutions with a concentration of 50ug / ml were added to the corresponding wells.
[0119] Step 3: Ultrasonic stimulation:
[0120] Eight hours after the addition of the materials, ultrasound stimulation was performed on the US, US+BTO, and US+BCZT / GO groups; the ultrasound parameters were set to 50% Duty Cycle, 1.0 MHz, and 1.5 W / cm 2 , lasting for 5 minutes. After the stimulation was completed, the well plate was returned to the cell culture incubator for continued culture. During the subsequent culture process, ultrasonic stimulation was repeated every two days until the 7th day.
[0121] The steps of BMSC inoculation, group culture and ultrasound stimulation are detailed to ensure experimental standardization. The group design is comprehensive, the material processing is accurate, and the ultrasound parameters are optimized to effectively promote cell differentiation research. Regular ultrasound stimulation simulates the physiological environment and enhances the experimental effect. This method provides a reliable platform for exploring the mechanism of BMSC osteogenic differentiation and the combined effect of materials and ultrasound, which will help promote the development of bone tissue engineering.
[0122] Among them, the continued culture and differentiation of BMSC in A2 refers to that after the ultrasonic stimulation is completed, the BMSC is placed in a constant temperature incubator at 37°C and 5% CO2 for continued culture to support its growth and differentiation process. During this period, the cell status is closely monitored and regularly checked to ensure that the culture environment is stable and suitable. At the end of the culture on the 7th day, the differentiation of BMSC in each group is observed, and special attention is paid to whether there are signs of differentiation into osteoblasts, such as changes in cell morphology, expression of specific markers, etc., to evaluate the effects of different treatment conditions on the osteogenic differentiation of BMSC.
[0123] Continuing to culture and differentiate BMSCs to ensure growth in a stable environment will help to further explore their osteogenic potential. Regularly monitor the cell status to promptly discover and adjust the culture conditions to ensure experimental accuracy. Differentiation observation on the 7th day can intuitively evaluate the effects of ultrasound and material treatment on BMSC osteogenic differentiation, providing valuable data and insights for bone tissue engineering.
[0124] The specific steps of detecting the differentiation of BMSC into osteoblasts by the Alizarin Red method in A3 are as follows:
[0125] Step 1: Sample preparation:
[0126] Remove the culture medium from the well plate and gently rinse the BMSC culture dish twice with PBS to remove the residual culture medium and impurities;
[0127] Step 2: Cell fixation:
[0128] Add an appropriate amount of 95% ethanol to each well and fix the cells for 10 minutes; after fixation, rinse the cells three times with double distilled water to remove residual ethanol;
[0129] Step 3: Alizarin red staining:
[0130] Add 0.1% Alizarin Red-Tris-HCl solution (pH 8.3) to each well, making sure that the solution covers the entire bottom of the well, and incubate the plate at 37°C for 30 minutes to allow Alizarin Red to combine with calcium salts in osteoblasts to form a red precipitate.
[0131] Step 4: Observe and record:
[0132] After staining, the cells were gently rinsed with double distilled water to remove unbound alizarin red dye; the red ALP-positive particles in the cytoplasm of osteoblasts were observed under a microscope, and the differentiation of cells in each group was recorded.
[0133] The Alizarin Red method is used to detect the osteogenic differentiation of BMSCs. The steps are clear and the operation is simple. Through fixation, staining and observation, the calcium salt deposition of osteoblasts can be visually displayed and the degree of differentiation can be evaluated. This method can not only effectively distinguish the differences in cell differentiation among groups, but also provide a reliable experimental basis for studying the osteogenic potential of BMSCs, which is of great significance for promoting the development of bone tissue engineering.
[0134] Example 1: The morphology of a novel piezoelectric nanomaterial of barium titanate loaded graphene oxide doped with zirconium and calcium (BCZT / GO) prepared by a hydrothermal method was observed by TEM. The specific operation steps are as follows:
[0135] Step 1: TEM sample preparation
[0136] Dispersion treatment: First, the target material (such as BCZT nanoparticles) is dispersed in ultrapure water at an appropriate concentration, and stirring or ultrasound is used to ensure that the nanoparticles are evenly and stably suspended in the water to form a suspension sample suitable for transmission electron microscopy (TEM) observation.
[0137] Select the support film: Select the appropriate support film according to the analysis requirements. Usually, a carbon film is used as a support film to carry and stabilize the sample. However, when energy dispersive X-ray spectroscopy (EDS) analysis is required to identify carbon elements, a silicon nitride film is used to avoid the interference of the carbon film itself on the analysis results.
[0138] Step 2: Sample loading and drying
[0139] Sample loading: Using a micropipette or dropper, take a few drops of sample from the prepared TEM suspension and gently drop them onto the prepared support film. Make sure the sample is evenly distributed and avoid aggregation.
[0140] Dry at room temperature: Place the support film loaded with the sample in a clean, dust-free environment and dry it naturally at room temperature. This process must ensure that the sample is completely dry to avoid blurring or interference with image quality during TEM observation.
[0141] Step 3: TEM analysis and element detection
[0142] Sample installation: Carefully place the dried sample (nanoparticles on the support film) on the sample rod of the TEM, and make fine adjustments to ensure that the sample position is stable and in the center of the observation window.
[0143] TEM morphology observation: The sample rod is placed into the TEM, and the high-resolution imaging function of the transmission electron microscope is used to carefully observe the morphology of the sample. During this process, parameters such as the acceleration voltage, focus, and magnification of the electron beam can be adjusted to obtain a clear sample image. For the BCZT nanoparticles in this example, it was observed that they were uniform and regular spherical, and the diameter was controllable within the range of 200-500nm.
[0144] EDS element analysis: The energy dispersive X-ray spectroscopy (EDS) module integrated on the TEM can be used to obtain the composition information of the elements in the sample. By scanning the sample area, collecting and analyzing the characteristic X-ray signals, the element distribution map can be drawn to reveal the uniform distribution of elements such as Ba, Ti, O, Zr, and Ca in BCZT nanoparticles. Figure 5 As shown, this process helps to further verify the chemical composition and structural characteristics of the samples.
[0145] Embodiment 2:
[0146] SEM was used to observe the surface morphology, aggregation state and particle size distribution of the three piezoelectric nanoparticles. The specific operation steps are as follows:
[0147] Step 1: Sample preparation and loading
[0148] Prepare the sample stage: First, firmly stick a small piece of conductive glue on the SEM dedicated sample stage. The conductive glue should be selected to ensure good electrical contact with the piezoelectric nanoparticles to reduce charging effects during SEM observation.
[0149] Spreading nanoparticles: Use a slender tool (such as a toothpick or a special sample disperser) to gently and evenly spread the dried piezoelectric nanoparticles (such as BCZT / GO) powder on the conductive glue. Pay attention to controlling the thickness of the spread to avoid too thick a layer that will cause unclear images or reduced resolution during observation.
[0150] Step 2: SEM observation and image acquisition
[0151] Vacuuming: Place the sample stage loaded with the sample into the sample chamber of the SEM and close the sample chamber door. Start the vacuum pump to evacuate the air in the SEM chamber to the required vacuum degree to reduce the scattering of the electron beam by air molecules and improve the image quality.
[0152] Setting parameters and observation: According to the characteristics of the piezoelectric nanoparticles to be observed and the performance of the SEM equipment, select appropriate parameters such as acceleration voltage and working distance. Start the SEM, adjust the lens to a clear focus, and start scanning and observing the sample. Pay attention to the surface morphology, aggregation state, and particle size distribution of the nanoparticles.
[0153] Image acquisition: When a satisfactory image is observed, use the image acquisition system attached to the SEM to take a photo and save the image. Ensure that the image is clear, without blur or distortion, for subsequent analysis.
[0154] Step 3: Particle size distribution calculation and analysis
[0155] Image import: Import the images taken by SEM into particle size analysis software such as Nano Measurer. These software usually have automatic or semi-automatic particle size measurement functions, which can accurately measure the diameter of particles in the image.
[0156] Particle size measurement: Set appropriate measurement parameters (such as threshold, minimum particle size, etc.) in the software to measure the particle size of piezoelectric nanoparticles (such as BCZT / GO) in the image. The software will automatically identify and measure the diameter of the particles and generate particle size distribution data.
[0157] Data analysis and reporting: Based on the particle size distribution data, statistical analysis is performed, such as calculating the average particle size, standard deviation, etc. At the same time, a particle size distribution histogram or curve chart can be generated to intuitively display the particle size distribution of nanoparticles. Finally, the analysis results are compiled into a report for subsequent research and application.
[0158] Embodiment 3:
[0159] The dried piezoelectric BCZT / GO nanoparticles were fixed on a sample plate and transferred to the analysis chamber after nitrogen pretreatment to ensure that the vacuum level in the pre-entry chamber met the standard. By carefully setting the spectral parameters, XPS measurements revealed the unique elemental composition of BCZT / GO, including the characteristic peaks of Ba 3d, Ca 2p, Ti 2p, O 1s, C 1s and Zr 3d, confirming the introduction of the Zr element and the coexistence of GO. The position of the Ti 2p and O1s peaks related to Ba-O-Ti and Ti-O-Ti further demonstrated the integrity of the BCZT structure. These detailed XPS data not only confirmed the successful synthesis of BCZT / GO nanoparticles, but also revealed the details of their surface chemical properties. Translated by DeepL.com (free version) Figure 6 shown.
[0160] Embodiment 4:
[0161] XRD is used to determine the crystal structure and composition of piezoelectric nanoparticles. The specific steps are as follows:
[0162] Step 1: Sample loading and preparation
[0163] Sample loading: Spread the completely dried piezoelectric nanoparticle powder (such as BCZT) gently and evenly on a dedicated XRD sample stage, making sure that the sample layer is neither too thick nor has voids, so that the X-rays can penetrate evenly and produce clear diffraction patterns.
[0164] Sample flatness and stability: Use appropriate tools (such as a tablet press or gentle tapping) to make the sample surface as flat as possible, and check whether the sample is firmly fixed on the sample stage to avoid movement or falling off during scanning.
[0165] Step 2: Scan parameter settings
[0166] Determine the scanning range: According to the expected crystal structure and composition of the piezoelectric nanoparticles, set the scanning angle range of the X-ray diffractometer to 10° to 90°, which can usually cover the main diffraction peaks of most inorganic materials.
[0167] Set the scanning speed: To balance the scanning time and the spectral resolution, select an appropriate scanning speed, such as 10° / min. A faster scanning speed can shorten the experimental time, but may sacrifice some details; a slower speed can provide a higher resolution spectrum, but it takes longer.
[0168] Step 3: Result Analysis
[0169] Data preservation: After completing the scan, save the acquired XRD spectrum data to ensure that the data is complete and correct.
[0170] Spectrum comparison and analysis: Use professional XRD analysis software to compare the experimental XRD spectrum with the data in the standard crystal database (such as JCPDS). By comparing the position (2θ angle) and relative intensity of the peaks in the spectrum, the crystal structure and phase composition of the sample can be determined.
[0171] Interpretation of results: In the XRD pattern of BCZT, special attention is paid to the (200) diffraction peak near 2θ=45°, which is a typical feature of the tetragonal phase of barium titanate. If only the peak corresponding to BaTiO3 appears in the spectrum and no other impurity peaks are observed, the sample is confirmed to be a pure phase or highly purified BCZT crystal structure according to JCPDS card number 05-0626, such as Figure 7 shown.
[0172] Embodiment 6:
[0173] The charge transfer of BCZT / GO is calculated by first-principles simulation. The specific steps are as follows:
[0174] In this study, we used the Vienna Ab initio Simulation Package (VASP) to treat the exchange-correlation potential using density functional theory (DFT) combined with generalized gradient approximation (GGA-PBE), and accurately simulated the interaction between ions and valence electrons using the projected augmented wave (PAW) method. The plane wave cutoff energy was set to 500 eV to ensure the calculation accuracy, and the structure was optimized to a Hermann-Feynman force less than The energy converges to 10^-5eV. To isolate the interlayer effect, a vacuum layer. During the relaxation process, a 3×3×3 Γ-centered k-point grid was used to cover the Brillouin zone. The dispersion force in the adsorption model was corrected using the DFT-D3 method. The analysis shows that the doping of Ca and Zr and the heterojunction formed with graphene oxide significantly promote the cross-transfer of electrons within the structure, enhance the interatomic electron overlap, and thus strengthen the covalency. In particular, the strong overlap between the 3d orbitals of metal elements (such as titanium) and the p orbitals of oxygen promotes orbital hybridization, which is key to the formation of covalent bonds. Ultimately, the richness of the total density of states is enhanced, revealing the enhancing effects of doping and heterojunction on conductivity and covalency, among which the introduction of Ca and Zr promotes the movement of the d orbital center of Ti to the Fermi level, such as Figure 8 , 9 , as shown in 10.
[0175] Embodiment 6:
[0176] The piezoelectric properties of piezoelectric nanoparticles were tested using a piezoelectric force response microscope. The specific steps are as follows:
[0177] The mesoporous red long afterglow nanogene carrier BCZT / GO was centrifugally separated and redispersed to prepare a scanning sample. The cantilever deflection was recorded by scanning technology and a three-dimensional image was obtained by software processing. PFM characterization showed that the BCZT / GO heterojunction exhibited significant piezoelectricity in the range of -11.4 to 12.8nm, and the phase contrast changed significantly under an applied voltage of 10V, reflecting the random distribution of ferroelectric domains. Its D33 value was as high as 72.836pm / V, which is 2.56 times that of BTO. Fig.11 , as shown in Figure 12, which demonstrates the significant enhancement of BCZT / GO in acoustic dynamic properties.
[0178] Embodiment 7:
[0179] The time-dependent photocurrents of different samples were measured by photoelectrochemistry (PEC). The specific operation steps are as follows:
[0180] PEC measurements of the Cu2-xO-BTO NC coating on the FTO substrate were performed using a three-electrode system (CHI 660E) under full-spectrum illumination. The results showed that the BCZT / GO heterostructure exhibited higher photocurrents than BTO and BCZT under full-spectrum illumination. In particular, the photocurrent density of BCZT / GO reached 0.4μA / cm 2 , twice that of pure BTO (0.2μA / cm 2 ), which shows that the BCZT / GO heterojunction effectively promotes the separation and transmission of photogenerated carriers and significantly improves the photoelectric conversion efficiency. Fig.13 shown.
[0181] Embodiment 9:
[0182] The Alizarin Red method was used to detect the differentiation of BMSC cells into osteoblasts. The specific steps are as follows:
[0183] In this study, bone marrow mesenchymal stem cells (BMSCs) were cultured in 24-well plates and adhered to the wall. They were then divided into a control group, an ultrasound (US) group, a BCZT / GO group, a US+BTO group, and a US+BCZT / GO group. Except for the control group, all groups were stimulated with ultrasound. The material-containing group (BCZT / GO, BTO) was added at a concentration of 50ug / ml and continued to be cultured until the 7th day after ultrasound stimulation, during which ultrasound treatment was performed regularly. The Alizarin red staining method was used to evaluate the differentiation of BMSCs into osteoblasts. The results showed that the US+BCZT / GO group significantly promoted osteogenic differentiation, as evidenced by an increase in red ALP-positive particles in the cytoplasm, such as Fig.14 As shown, this combination has potential application prospects in the field of bone regeneration.
[0184] It should be noted that, in this article, relational terms such as first and second, etc. are only used to distinguish one entity or operation from another entity or operation, and do not necessarily require or imply any such actual relationship or order between these entities or operations. Moreover, the terms "include", "comprise" or any other variants thereof are intended to cover non-exclusive inclusion, so that a process, method, article or device including a series of elements includes not only those elements, but also other elements not explicitly listed, or also includes elements inherent to such process, method, article or device.
[0185] Although embodiments of the present invention have been shown and described, it will be appreciated by those skilled in the art that various changes, modifications, substitutions and variations may be made to the embodiments without departing from the principles and spirit of the present invention, and that the scope of the present invention is defined by the appended claims and their equivalents.
Claims
1. A method for inducing osteogenic differentiation of bone marrow mesenchymal stem cells using ultrasonic piezoelectric materials, characterized in that: The specific steps of the preparation method are as follows: S1: Preparation of solution; TiCl4 and ZrCl2 were dissolved in anhydrous ethanol and deionized water, mixed and magnetically stirred at 100°C for 30 minutes to promote the reaction, then the pH was adjusted and NaOH and PVP were added, stirred for 10 minutes to help the formation of nanomaterials; S2: Introduction of graphene oxide and doping ions: After GO is dispersed, ultrasonic treatment is performed, and CaCl2 and ZrCl2 are added for stirring, so that the doping ions are evenly distributed on the GO surface and solution; S3: hydrothermal reaction and post-treatment: The product was obtained by hydrothermal reaction at 180°C / 12h, washed to neutrality, and dried at 80°C to obtain barium titanate / GO doped calcium zirconium piezoelectric material.
2. The method for inducing osteogenic differentiation of bone marrow mesenchymal stem cells using ultrasonic piezoelectric materials according to claim 1, characterized in that: The specific steps of introducing graphene oxide and doping ions in S2 are as follows: Step 1: Dispersion of graphene oxide Accurately weigh 100 mg of GO and slowly add it to 30 mL of deionized water; The mixed solution was ultrasonicated using an ultrasonic processor for 10 minutes to ensure that GO was evenly dispersed in water to form a stable GO dispersion; Step 2: Preparation of doping ions Accurately weigh 0.166 g of CaCl2 and 0.373 g of ZrCl2-7H2O; Add the two salts separately or simultaneously into an appropriate amount of deionized water to ensure complete dissolution; Step 3: Mixing and stirring of doping ions Slowly add the doping ion solution prepared in step 2 to the GO dispersion prepared in step 1; The mixed solution was stirred using a magnetic stirrer at 100 rpm and 100 °C for 30 min. This step was intended to allow the doping ions to be evenly distributed on the surface of GO and throughout the solution, promoting their interaction with GO and possible doping processes.
3. The method for inducing osteogenic differentiation of bone marrow mesenchymal stem cells using ultrasonic piezoelectric materials according to claim 1, characterized in that: The specific steps of the hydrothermal reaction and post-treatment in S3 are as follows: Step 1: Hydrothermal reaction Carefully transfer all the mixed solutions to the high-temperature hydrothermal reactor to ensure that no solution remains; Seal the reactor and adjust the heating system to gradually raise the internal temperature of the reactor to 180 degrees Celsius; The reaction was maintained at this temperature for 12 hours, during which time barium titanate grew on the surface of GO and was doped with calcium and zirconium to form the desired nanocomposite material; Step 2: Washing the precipitate After the reaction is completed, the reactor is cooled naturally to room temperature, and the product is taken out of the reactor. The product is repeatedly washed with deionized water to remove residual unreacted substances, ions and other impurities. Then, it is further washed with anhydrous ethanol until the pH value of the washing liquid reaches 7, indicating that the precipitate has been washed clean. Step 3: Drying The washed precipitate is transferred to a dry and clean container; the container is placed in an oven at 80°C for drying for 12 hours; after drying, the product is taken out to obtain the final piezoelectric nanomaterial of barium titanate loaded with graphene oxide and doped with calcium and zirconium.
4. The method for inducing osteogenic differentiation of bone marrow mesenchymal stem cells using ultrasonic piezoelectric materials according to claim 1, characterized in that: The piezoelectric material prepared based on the above preparation method has the characteristic of self-generating electricity under the action of ultrasound to induce the osteogenic differentiation of bone marrow mesenchymal stem cells (BMSC) to achieve the repair of dental pulp damage, wherein the steps of bone marrow cell stimulation and detection method are as follows: A1: BMSC inoculation, group culture and ultrasonic stimulation; BMSC were inoculated in 24-well plates and cultured and then divided into five groups. The material group was added with 50ug / ml solution. After 8 hours, the US group and the material + US group were ultrasonicated according to the set parameters, and the process was repeated every other day until the 7th day. A2: Continued culture and differentiation of BMSCs: BMSCs were continuously cultured after ultrasound and the signs of osteogenic differentiation were observed for 7 days; A3: Alizarin red method to detect BMSC differentiation into osteoblasts: Alizarin red was used to stain BMSC to measure osteogenic differentiation, and the red particles were observed under a microscope to record the differentiation.
5. The method for inducing osteogenic differentiation of bone marrow mesenchymal stem cells using ultrasonic piezoelectric materials according to claim 4, characterized in that: The specific steps of inoculation, group culture and ultrasonic stimulation of BMSCs in A1 are as follows: Step 1: Cell inoculation and culture: Bone marrow mesenchymal stem cells were evenly seeded into a 24-well plate with a moderate cell density in each well; The well plate was placed in a cell culture incubator at 37°C and 5% CO2 for 24 hours until the cells adhered; Step 2: Grouping and material processing: The cells were divided into five groups: control group, US group, BCZT / GO group, US+BTO group, and US+BCZT / GO group; for the groups containing materials (BCZT / GO, US+BTO, and US+BCZT / GO), material solutions with a concentration of 50ug / ml were added to the corresponding wells; Step 3: Ultrasonic stimulation: Eight hours after the addition of the materials, ultrasound stimulation was performed on the US, US+BTO, and US+BCZT / GO groups; the ultrasound parameters were set to 50% Duty Cycle, 1.0 MHz, and 1.5 W / cm 2 , lasting for 5 minutes. After the stimulation was completed, the well plate was returned to the cell culture incubator for continued culture. During the subsequent culture process, ultrasonic stimulation was repeated every two days until the 7th day.
6. The method for inducing osteogenic differentiation of bone marrow mesenchymal stem cells using ultrasonic piezoelectric materials according to claim 4, characterized in that: The continued culture and differentiation of BMSC in A2 refers to that after the ultrasonic stimulation is completed, the BMSC are placed in a constant temperature incubator at 37°C and 5% CO2 for continued culture to support their growth and differentiation process. During this period, the cell status is closely monitored and regularly checked to ensure that the culture environment is stable and suitable. At the end of the 7th day of culture, the differentiation of BMSC in each group is observed, with special attention paid to whether there are signs of differentiation into osteoblasts, such as changes in cell morphology and expression of specific markers, to evaluate the effects of different treatment conditions on the osteogenic differentiation of BMSC.
7. The method for inducing osteogenic differentiation of bone marrow mesenchymal stem cells using ultrasonic piezoelectric materials according to claim 4, characterized in that: The specific steps of the Alizarin Red method in A3 for detecting the differentiation of BMSC into osteoblasts are as follows: Step 1: Sample preparation: Remove the culture medium from the well plate and gently rinse the BMSC culture dish twice with PBS to remove the residual culture medium and impurities; Step 2: Cell fixation: Add an appropriate amount of 95% ethanol to each well and fix the cells for 10 minutes; after fixation, rinse the cells three times with double distilled water to remove residual ethanol; Step 3: Alizarin red staining: Add 0.1% Alizarin Red-Tris-HCl solution (pH 8.3) to each well, making sure that the solution covers the entire bottom of the well, and incubate the plate at 37°C for 30 minutes to allow Alizarin Red to bind to calcium salts in osteoblasts to form a red precipitate; Step 4: Observe and record: After staining, the cells were gently rinsed with double distilled water to remove unbound alizarin red dye; the red ALP-positive particles in the cytoplasm of osteoblasts were observed under a microscope, and the differentiation of cells in each group was recorded.